Category Stretching: Reorienting Research on Categories in Strategy, Entrepreneurship, and Organization Theory - Durand, Rodolphe; Paolella, Lionel (Journal of Management Studies, 2013)
abstractWe advocate for more tolerance in the manner we collectively address categories and categorization in our research. Drawing on the prototype view, organizational scholars have provided a ‘disciplining’ framework to explain how category membership shapes, impacts, and limits organizational success. By stretching the existing straightjacket of scholarship on categories, we point to other useful conceptualizations of categories – i.e. the causal‐model and the goal‐based approaches of categorization – and propose that depending on situational circumstances, and beyond a disciplining exercise, categories involve a cognitive test of congruence and a goal satisfying calculus. Unsettling the current consensus about categorical imperatives and market discipline, we suggest also that audiences may tolerate more often than previously thought organizations that blend, span, and stretch categories. We derive implications for research about multi‐category membership and mediation in markets, and suggest ways in which work on the theme of categories in the strategy, entrepreneurship, and managerial cognition literatures can be enriched.